HUBUNGAN KEAKTIFAN DALAM HIMA PRODI PPKN DENGAN INDEKS PRESTASI MAHASISWA PPKN UNIVERSITAS PGRI ADI BUANA SURABAYA - Suhartono, Suhartono (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2018)
This research was motivated by a student organization requires students to be active and independent role in running the holding organization. Students are expected to be able to contribute through his thinking in a student organization. The problem of this research is